Metsulfuron-methyl and glyphosate transport in a mollisol soil in the pampean region of Argentina - Gonzalo Mayoral, Eliana Soledad (2021)
The agricultural activity poses the potential risk of contaminating groundwater resources because of t he leaching capacity of the agrochemicals used. Glyphosate and metsulfuron-methyl are two herbicides widely used in the Pampean region of Argentina. The objective of this study was to evaluate the vertical transport of both herbicides in the soil profile of a typic Argiudoll, under laboratory conditions. Bromide (equivalent to 1500 kg ha-1 ) was used as a non-reactive solute, and metsulfuron-methyl (equivalent to 10 g ha-1 of the active ingredient, a.i.) and glyphosate (equivalent to 5 kg ha-1 of a.i.) were used as reactive solutes. Six replicates per horizon were used. The transport parameters were estimated using the convection-dispersion equation (CDE) and analysed using mixed models. A preferential flow by macropores was the mechanism dominating the transport of the substances in the horizons under study. The following recovery percentages were found in effluents: bromide 72.4, 83.75 and 90.49%, metsulfuron-methyl 51.7, 56.5 and 67.0%, and glyphosate 0.75, 1.76 and 0% in horizons A, B and C, respectively. Metsulfuron-methyl presented higher leaching capacity in the horizons studied than glyphosate, which was retained in the first centimetres of each column. Thus, metsulfuron-methyl poses a high potential risk of contaminating groundwater, as opposed to glyphosate, which involves a low to negligible risk.